2014
DOI: 10.1136/tobaccocontrol-2013-051200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical interventions to reduce secondhand smoke exposure among pregnant women: a systematic review

Abstract: Objective To conduct a systematic review of clinical interventions to reduce secondhand smoke (SHS) exposure among non-smoking pregnant women. Data sources We searched 16 databases for publications from 1990 to January 2013, with no language restrictions. Study selection Papers were included if they met the following criteria: (1) the study population included non-smoking pregnant women exposed to SHS, (2) the clinical interventions were intended to reduce SHS exposure at home, (3) the study included a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…Studies (41-45) have consistently found that higher cigarette taxes reduce the prevalence of prenatal smoking and the number of LBW, PTB and SIDS cases, and two studies (42, 43) found the highest price sensitivity for younger pregnant women. Medicaid policies supporting pharmacotherapy and behavioral therapy (46, 47) and more generally behavioral interventions (48, 49) have been found effective in reducing prenatal smoking. Other potentially effective policies are raising the minimum legal purchase age for tobacco to 21 (50), and media campaigns and graphic health warnings directed at discouraging maternal smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (41-45) have consistently found that higher cigarette taxes reduce the prevalence of prenatal smoking and the number of LBW, PTB and SIDS cases, and two studies (42, 43) found the highest price sensitivity for younger pregnant women. Medicaid policies supporting pharmacotherapy and behavioral therapy (46, 47) and more generally behavioral interventions (48, 49) have been found effective in reducing prenatal smoking. Other potentially effective policies are raising the minimum legal purchase age for tobacco to 21 (50), and media campaigns and graphic health warnings directed at discouraging maternal smoking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, demand studies 30,31,32,33,34 have obtained prenatal prevalence price elasticities between -0.13 and -0.7, which are consistent with the elasticities used in SimSmoke, and a recent study 34 found higher elasticities for those of low socioeconomic status. Studies have found that other tobacco control policies, including cessation treatment 35,36 , smoke-free air laws 26 , and media campaigns 37 , are effective at reducing prenatal smoking.…”
Section: The Effect Of Policiesmentioning
confidence: 99%
“…30 Although very few studies have evaluated the effectiveness of interventions to reduce SHS exposure during pregnancy, 37 it appears that such interventions have the potential to improve birth outcomes, which include reducing the incidence of very low birthweight and very preterm birth. 38 This suggests that, similar to the perinatal health risks associated with active smoking during pregnancy, those related to SHS exposure are indeed avoidable.…”
Section: Smoke-free Legislation and Child Health: Likely Causal Pathwaysmentioning
confidence: 99%